Metastatic basal cell carcinoma with atypical pattern of spread - Gellatly, Matthew; Cruzval-O'Reilly, Estefanía; Mervak, Julie E.; Mervak, Benjamin M. (Radiology case reports, 2020)
Basal cell carcinoma is the most common malignancy in the United States. However, metastasis of basal cell carcinoma is exceedingly rare, with incidence estimates of 0.0028–0.055%. When it does metastasize, basal cell carcinoma most commonly spreads to regional lymph nodes and lungs, although other sites of disease can occur. This case report presents multi-modality imaging of a 54-year-old male who developed multifocal metastatic basal cell carcinoma approximately three years after initial presentation with an ulcerated groin lesion. Ultimately, metastases included many common and uncommon sites, including lymph nodes, lung, duodenum, spleen, and adrenal glands. This case provides an interesting example of an uncommon pattern of spread and associated symptoms of treatment-resistant metastatic basal cell carcinoma.